Removal of acetic acid from aqueous solution by polyethersulfone supported liquid membrane - Norlisa, Harruddin; Syed Mohd Saufi, Tuan Chik; C. K. M., Faizal; Abdul Wahab, Mohammad (AIDIC Servizi, 2017)
Lignocellulosic biomass can be converted to biofuel, which is one of the renewable energy. To achieve this purpose, acid hydrolysis was used to hydrolyse lignocellulosic materials to fermentable sugars. However, acetic acid, a major inhibitory compound was released during the acid hydrolysis process. Existence of acetic acid significantly suppressed fermentative organisms and decreased the production of ethanol. It is necessary to remove acetic acid inhibitor from biomass hydrolysate prior to the fermentation process. Selective removal of acetic acid from aqueous solution was attempted by using supported liquid membrane (SLM) system based on tri-n-octylamine carrier and sodium hydroxide stripping phase. Polyethersulfone (PES) membrane was prepared by vapour induced phase separation method and used as a matrix support in SLM process. Effects of PES membrane thickness, types of diluent, and flow rate of feed phase were tested. Under favourable condition, almost 86 % of acetic acid was successfully removed from the aqueous solution. The PES SLM system remained stable for 8 h of extraction without any breakage.